Front Cover: Designing Sodium Manganese Oxide with 4 d‐Cation Zr Doping as a High‐Rate‐Performance Cathode for Sodium‐Ion Batteries (ChemElectroChem 12/2020). Issue 12 (18th May 2020) - Shi, Wen‐Jing; Zheng, Ya‐Min; Meng, Xiao‐Meng; Liu, Shi‐Bin; Xu, Shou‐Dong; Chen, Liang; Wang, Xiao‐Min; Zhang, Ding
Abstract : The Front Cover shows that 4d‐cation Zr substitution greatly promotes the electrochemical performance of tunnel‐type transition metal oxides, making them promising cathodes for sodium‐ion batteries. Zr introduction not only facilitates Na + diffusion kinetics but also decreases the structural changes during the electrode process, thus resulting in superior high‐rate performance and long cyclic stability. More information can be found in the Article by W.‐J. Shi et al .